Liposome Adjuvants: Simultaneous Induction of Innate and Adaptive Immunity is Key to Success - Syed M Faisal (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
The current generation vaccines are mainly composed of highly purified antigens and tend to be poorly immunogenic, requiring potent adjuvants for their success. The adjuvants currently available suffer from various drawbacks such as low potency (inability to activate strong humoral and cell-mediated immune response) and extreme toxicity for routine clinical use in humans. In addition, not all adjuvants are effective for all antigens. The compromise between the requirement for strong adjuvant activity and an acceptable low level of toxicity has left us with limited choice of adjuvants. Although alum adjuvant has been used for decades, it is associated with severe local reaction and is unable to activate cell-mediated immunity, hence has proven unsuccessful against intracellular infections [1]. Therefore, it is very important to identify new adjuvants or improve the existing ones. The ideal adjuvant would be one that apart from activating strong humoral and cell-mediated immune response, has negligible toxicity to the host.